Proceedings of the International Working Conference on Advanced Visual Interfaces 2016
DOI: 10.1145/2909132.2909282
|View full text |Cite
|
Sign up to set email alerts
|

Touchless Interfaces For Public Displays

Abstract: Public displays have lately become ubiquitous thanks to the decreasing cost of such technology and public policies supporting the future development of smart cities. Depending on form factor, those displays might use touchless gestural interfaces that therefore are becoming more often the object of public and private research. In this paper, we focus on touchless interactions with situated public displays, and introduce a pilot study on comparing two interfaces: an interface based on the Microsoft Human Interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The display runs an application that employs an Avatar-based touch-less gestural interface, built as an extension of the interface described in [6]. The layout consists of an Avatar placed in the middle of the screen, with all the other interface components arranged around it (see Figure 2).…”
Section: Display Applicationmentioning
confidence: 99%
“…The display runs an application that employs an Avatar-based touch-less gestural interface, built as an extension of the interface described in [6]. The layout consists of an Avatar placed in the middle of the screen, with all the other interface components arranged around it (see Figure 2).…”
Section: Display Applicationmentioning
confidence: 99%
“…For instance, Müller et al showed that interactivity can be recognized after less than three seconds using avatars [23]; however, their work considers users of various ages, without an in-depth analysis of children's behaviors. Similar limitations can be found in [8,17,18,33]. In the context of child-computer interaction, other facets of touchless gestural interaction have been investigated, mainly in order to understand the effect of such novel paradigm in learning activities [1,5,26], but also for gaming purposes [4,5,12].…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 94%
“…In the context of pervasive displays research, many touchless gestural interfaces have been proposed and implemented. They have been used in order to interact with 3D virtual objects [6], to access information provision systems [7,18], to create and support playful interactions [23], and have many other applications. The use of touchless gestures, especially when applied to public displays, has many advantages.…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 99%
See 2 more Smart Citations